Islam Wasathiyah To Build A Dignified Indonesia (Efforts To Prevent Radical - Terrorism) - Amirsyah Tambunan (ADI Journal on Recent Innovation, 2019)
Muslims in Indonesia in Indonesia face global challenges in the form of liberalism in variousdimensions of life. Therefore, Muslims can express their aspirations through the known 411action, 212 in a peaceful manner. Various parties respect Muslims, because they are able toprove Muslims who agree in Indonesia. Carrying out Islam wasathiyah (moderate), so as not tocause anarchy.However important prevention efforts that promote Islam as a religion of mercy to all the worlds(Islam rahmata lil 'alamin) through understanding of Islam washatiyah, to avoid understandingthe extreme form of terrorism, anarchism, separatism and other forms of destructive life ofsociety, nation and state.